1998
DOI: 10.1099/0022-1317-79-8-1983
|View full text |Cite
|
Sign up to set email alerts
|

Bovine herpesvirus type 1 glycoprotein H is essential for penetration and propagation in cell culture.

Abstract: Bovine herpesvirus type 1 (BHV-1) glycoprotein H (gH) is a structural component of the virion which forms a complex with glycoprotein gL. To study the role of BHV-1 gH in the virus infectious cycle, a gH null mutant was constructed in which the gH coding sequences were deleted and replaced by the Escherichia coli lacZ cassette. The BHV-1 gH null mutant was propagated in trans-complementing MDBK cells, stably transfected with plasmid pMEP4 containing the BHV-1 gH gene under the control of the inducible mouse me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Essentially all of the gH homologs that have been studied to date in many different herpesviruses have been implicated as playing a role in virus penetration, and null mutants have been made to confirm this role in herpes simplex virus (7), pseudorabies virus (1,29), and bovine herpesvirus 1 (21,30). The evidence for involvement of the EBV gH in penetration has been indirect.…”
Section: Discussionmentioning
confidence: 99%
“…Essentially all of the gH homologs that have been studied to date in many different herpesviruses have been implicated as playing a role in virus penetration, and null mutants have been made to confirm this role in herpes simplex virus (7), pseudorabies virus (1,29), and bovine herpesvirus 1 (21,30). The evidence for involvement of the EBV gH in penetration has been indirect.…”
Section: Discussionmentioning
confidence: 99%
“…After this high affinity interaction between gD and cell receptors, the subsequent virus penetration occurs by fusion of the virion envelope with plasma membrane. This crucial process requires at least the involvement of four BoHV-1 glycoproteins: gD [111,114], gB [58] and the heterodimer formed by gH and gL [131].…”
Section: Bohv-1 Replication In the Cellmentioning
confidence: 99%
“…Several constructions of mutant viruses have shown that gC, gI, gE, gG and gM are non essential glycoproteins [8,65]. On the contrary, the deletion of the gene encoding either gB or gD or gH reduces the capacity of in vitro replication [44,80]. Glycoproteins L and K are essential in HSV-1 and this is very likely to be the case in the other alphaherpesviruses [54,104].…”
Section: Viral Glycoproteinsmentioning
confidence: 99%
“…BoHV-1 and BoHV-5 gH are both expressed as early-late proteins. Glycoprotein H is essential for both penetration and cell-to-cell spread [7,80,81]. In CpHV-1, gD shows a relatively high homology to BoHV-1 gD amino acid sequences (similarity of 68.8%) and has a molecular mass similar to BoHV-1 gD.…”
Section: Viral Glycoproteinsmentioning
confidence: 99%